THE CUPRITE-LIKE FRAMEWORK OF OCU4 TETRAHEDRA IN THE CRYSTAL STRUCTURE OF SYNTHETIC MELANOTHALLITE, CU2OCL2, AND ITS NEGATIVE THERMAL EXPANSION - Krivovichev S.V.; Filatov S.K.; Burns P.C. (My University, 2002)
Crystals of synthetic melanothallite, Cu 2 OCl 2 , have been prepared by chemical transport reactions. Its crystal structure (orthorhombic, Fddd, a 7.4691(15), b 9.5969(19), c 9.700(2) Å, V 695.3(2) Å 3 , Z = 8) has been refined to R 1 = 0.028 (wR = 0.078; S = 1.180) on the basis of 346 unique observed reflections (|F o | ≥ 4 F). There is one symmetrically independent Cu atom in the structure, coordinated by two O and four Cl atoms. The mixed-ligand CuO 2 Cl 4 octahedron shows strong Jahn–Teller (4 + 2)-distortion, with two O and two Cl atoms located in the equatorial plane and two Cl atoms in apical positions. The structure may be described as a three-dimensional framework formed by the cross-linking of chains of edge-sharing CuO 2 Cl 2 squares. The chains are parallel to [110] and [¯ 110], and are linked to each other through the sharing of O atoms. The structure can also be described as an array of OCu 4 oxocentered tetrahedra linked by the sharing of Cu corners into a cuprite-like three-dimensional framework, with cavities in the framework containing Cl anions. As established previously, melanothallite shows negative thermal expansion along the b axis of its unit cell (b = –26.7 10 –6 °C –1), whereas thermal expansion along the a axis is positive and large (a = 50.6 10 –6 + 25.2 10 –9 t °C –1). This thermal behavior is explained on the basis of a cross-linking of chains of edge-sharing CuO 2 Cl 2 squares. In the room-temperature structure, two chains are inclined to each other by ~76°. When the temperature increases, the angle tends toward 90°, and the change of the angle between the two chains is accompanied by an increase of the a unit-cell parameter and by a decrease in the b parameter. This hinge mechanism provides an explanation for the high anisotropy in the thermal behavior of melanothallite observed by X-ray powder-diffraction methods.
Keywords: melanothallite; crystal structure; cuprite; oxocentered tetrahedra